Digital Underwater Acoustic Communication Simulator - Sampaio, David (2019)
The Underwater acoustic communication is still a relatively new term both for students and for researchers. The two thirds of water that cover our planet continuous to have much to give, and the rising interest on the oceans will continue on the future. As the interest increase, increases too the will of the researchers in use the oceans as a means, a channel of communication that can be effectively used. As we will see, this is a challenge task, fist because electromagnetic waves cannot be used in the underwater environment, so insisted of electromagnetic waves this study is turned to the study of acoustic waves and its performance on the underwater environment. As will related in this paper there are various challenges that will be explained one by one. In the first chapter there will be discussed the theories and the underwater channel properties, as well the MIMO system that implies the use of more than one antenna to transmit and receive in a way that the signal we want to send reaches de destination with substantial performance. The last chapter will be more focused on the simulation of that communication channel and its results will become clearer.